2020
DOI: 10.3390/nano10071250
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Performance of Aqueous Solution-Processed Cu2ZnSn(S,Se)4 Photovoltaic Materials by Mn2+ Substitution

Abstract: In this work, the Cu2MnxZn1−xSn(S,Se)4 (0 ≤ x ≤ 1) (CMZTSSe) alloy films were fabricated by a sol-gel method. Meanwhile, the effects of Mn substitution on the structural, morphological, electrical, optical, and device performance were studied systematically. The clear phase transformation from Cu2ZnSn(S,Se)4 (CZTSSe) with kesterite structure to Cu2MnSn(S,Se)4 (CMTSSe) with stannite structure was observed as x = 0.4. The scanning electron microscope (SEM) results show that the Mn can facilitate the grain growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In addition, we found that the content of Sn decreased with the increase in x value in Table . In the process of selenization, the loss of Sn is inevitable, leading to the decrease of the Sn content, which has been reported in the literature . The decrease of the Zn and Sn content results in the increase of Cu/(Zn + Ni + Sn) ratio and the decrease of (Ni + Zn)/Sn ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we found that the content of Sn decreased with the increase in x value in Table . In the process of selenization, the loss of Sn is inevitable, leading to the decrease of the Sn content, which has been reported in the literature . The decrease of the Zn and Sn content results in the increase of Cu/(Zn + Ni + Sn) ratio and the decrease of (Ni + Zn)/Sn ratio.…”
Section: Resultsmentioning
confidence: 99%
“…In the process of selenization, the loss of Sn is inevitable, leading to the decrease of the Sn content, which has been reported in the literature. 37 The decrease of the Zn and Sn content results in the increase of Cu/(Zn + Ni + Sn) ratio and the decrease of (Ni + Zn)/Sn ratio. It is well known that the energy required to form Cu Zn antiposition defects in the CZTSSe lattice is very low.…”
Section: Effect Of Ni Doping Concentration On Thementioning
confidence: 99%
“…Therefore, the Eg of CNZTSSe will be closer to the small Eg of CZTSe as the Se content rises. Moreover, according to the first principal calculation, when Se replaces S, the orbital interaction between the valence band (VBM) top and the conduction band (CBM) bottom is weakened, thus reducing Eg (i.e., CBM = VBM + Eg) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…An efficient charge separation process at the PN heterojunction is very imperative for the effective operation of solar cells. The recombination at the PN heterojunction due to interface defects and poor band alignment is unfavorable for efficient solar cells. , The optimization of PN heterojunctions is the focal point of kesterite CZTS research. The performance of solar cells can be improved via heterojunction engineering, cation doping, interfacial engineering, and passivation layer. The Cd-free Al 2 O 3 passivating layer and band-gap-controlled (Zn,Sn)O buffer layer enable CZTS and CZTSSe optoelectronic conversion gadgets with greater than 10% efficiency, displaying a captivating industrial value.…”
Section: Introductionmentioning
confidence: 99%
“…The recombination at the PN heterojunction due to interface defects and poor band alignment is unfavorable for efficient solar cells. 7,8 The optimization of PN heterojunctions is the focal point of kesterite CZTS research. The performance of solar cells can be improved via heterojunction engineering, cation doping, interfacial engineering, and passivation layer.…”
Section: Introductionmentioning
confidence: 99%